The Relationship between Hypercholesterolemia and Hyperuricemia, Elevated Body Mass Index, and Hypertension in Climacteric Women - Ismawati; Sara Puspita; Regina Cintya Darajat; Fitri Rahmawati (Global Medical & Health Communication (GMHC), 2025)
The climacteric phase marks the transition from perimenopause to postmenopause, which is triggered by ovarian aging and declining estrogenic levels. During this phase, women face an increased risk of metabolic disorders. This study aimed to investigate the relationships among total cholesterol and uric acid levels, body mass index (BMI), and blood pressure among climacteric women residing in the Tamansari Public Health Centre area, Bandung City. An analytical observational study with a cross-sectional design was conducted using purposive sampling in the Tamansari Public Health Centre area, Bandung City, during October 2024. A total of 66 climacteric women aged over 42 years, without prior diagnoses of metabolic disorders and not receiving related treatments, were included. Data collection comprised anthropometric measurements, self-reported menstrual status, and capillary blood examinations of total cholesterol and uric acid levels using a standardized point-of-care testing (POCT) device. Hypercholesterolemia was defined as total cholesterol ≥200 mg/dl, hyperuricemia as serum uric acid ≥6 mg/dl, elevated BMI as ≥25 kg/m2, and hypertension as blood pressure ≥140/90 mmHg. Statistical analysis was performed using Fisher’s exact test, with p<0.05 considered significant. The mean age of participants was 49.6±4.7 years. Mean total cholesterol was 215±44 mg/dl, serum uric acid 6.1±1.6 mg/dl, BMI 27.3±4.9 kg/m2, and systolic/diastolic blood pressure 128±16 / 81±10 mmHg. No significant associations were found between hypercholesterolemia and hyperuricemia (p=0.999), elevated BMI (p=0.159), or hypertension (p=0.275). This study concludes that hypercholesterolemia was not significantly associated with hyperuricemia, elevated BMI, or hypertension among climacteric women in the Tamansari Public Health Centre area of Bandung City.